Exploring pandemic preparedness through public perception and its impact on health service quality, attitudes, and healthcare image - Onur İzmir; Reda M. Lebcir; Oğuz Oypan (Scientific Reports)
Abstract Pandemic preparedness has gained increased significance in public health following the COVID-19 pandemic. Traditionally, it has been assessed from an internal organizational perspective, focusing on health sector readiness and addressing shortcomings. However, this perspective often overlooks the public’s perception of preparedness and its influence on behaviors within the healthcare sector. This study investigates how public views on pandemic preparedness shape attitudes, behaviors, and the image of the healthcare industry, which are critical in determining how individuals interact with health entities and respond to public health advice during a pandemic. To explore this, a set of hypotheses linking pandemic preparedness with health service quality, attitudes, and healthcare image was formulated. An online survey conducted in Türkiye gathered 322 responses. Hypothesis testing was performed using Structural Equation Modeling. The findings suggest that pandemic preparedness significantly impacts health service quality, public attitudes, and the image of the healthcare system during pandemic conditions. These results highlight the need to consider public perceptions of preparedness and their effects on behavior. Proactive communication strategies and public involvement in preparedness planning are essential for fostering a collective and informed response to the challenges posed by pandemics.